The human papillomavirus Test of Cure: A lesson on compliance with the NHMRC guidelines on screening to prevent cervical cancer. (14th April 2015) - Munro, Aime; Spilsbury, Katrina; Leung, Yee; O'Leary, Peter; Williams, Vincent; Codde, Jim; Steel, Nerida; Cohen, Paul; Semmens, James
<x xml:space="preserve">Abstract</x> Background In Australia, high‐risk human papillomavirus (HR HPV) testing is recommended for follow‐up of women treated for a high‐grade squamous intra‐epithelial lesion (HSIL). The sensitivity of HR HPV testing is critical to identify women at risk of further high‐grade cervical disease. In Australia, this management protocol is known as the 'Test of Cure' (ToC). Aim To conduct a population‐based study investigating practitioners' compliance with ToC. Materials and Methods Women treated for an HSIL between the five‐year period 01 Jan 2006 to 31 Dec 2010 were identified and followed up for at least a 27‐month period. Proportions and relative odds were determined for women entering and completing the ToC management pathway within recommended time frames. Results There were 5, 194 women identified as 'eligible' to enter the ToC management pathway. Of these, 1, 916 (37%) were managed with annual Pap smears and never had a HR HPV test performed. There were 1, 296 (25%) women who entered the ToC management pathway within recommended time frames, and a further 1, 978 (38%) women entered outside of the recommended time frames. Overall, 961 women completed the ToC and were classified as 'cured' and were eligible to return to two‐yearly Pap smears. Women's demographic information was significantly associated with ToC commencement, specifically, age and year of treatment, and Index of Relative Socioeconomic Disadvantage. Conclusion Overall, a significant number of Australian women did not enter ( 37%) and complete ( 50%) the ToC management pathway. The challenge remains to advocate its use to practitioners to ensure women are returned to the population screening interval in a timely manner.